The Effect of the Mesoparasitic Barnacle Anelasma on the Development of Reproductive Organs of Deep-sea Squaloid Sharks, Centroscyllium and Etmopterus - Yano, Kazunari; Musick, John A. (Environmental biology of fishes, 2000)
Specimens of the mesoparasitic barnacle, Anelasma, were found attached to several host deep-sea squaloid sharks, Centroscyllium fabricii from off Greenland, Etmopterus princeps from the Canary Islands, and Etmopterus unicolor and Etmopterus granulosus from Three Kings Ridge and Louisville Ridge near New Zealand. One to three parasites were partially embedded in each host shark in the head, mouth, bases of 1st and 2nd dorsal fins, pectoral and pelvic fins, caudal fin, abdomen or claspers. Testes and claspers of parasitized mature-sized males were less developed than those of non-parasitized mature males. The ova of parasitized females of mature size were small and whitish-yellow compared to the large yellow ova of non-parasitized mature females. The number of mature ova in a parasitized specimen was lower than expected in relation to a non-parasitized individual of the same size. Attachment of parasitic barnacles appeared to retard the development of reproductive organs of host sharks.